Thermal processing of equine milk – A review - Papademas, Photis; Neokleous, Ioanna; Mousikos, Panayiotis (My University, 2023)
Equine (donkey, mare) milk has been known to certain parts of the world since antiquity. It has been traditionally consumed raw or fermented because of its unique chemical composition (similar to human milk) and nutritional value, linking it to positive health impact. There is an identified consumer need for equine milk, hence effective farm management is essential to increase milk production and meet food safety legislation. This has led to the employment of several treatments such as thermal (i.e., pasteurisation), preservation (i.e., spray-drying), dairy product manufacture (i.e., cheese, yoghurt) to increase shelf-life, product availability and diversity. The effect of different heat treatments on equine milk constituents such as whey proteins, caseins and the role of minerals, salts and their impact on coagulation and digestibility of the milk is reviewed. More research is required to explain the different phenomena responsible for conformational and other changes during heat treating of equine milk.
Keywords: Farms; Chemical compositions; Consumer's needs; Farm management; Food-safety; Health impact; Human milk